Education and creativity. - Foxell, Simon, ....-; Mitchell, William J., ....- (London : Black Dog, 2008)
Education and Creativity - two views on the future of education. Simon Foxell examines the possible outcomes of current government policy for personalised learning in an increasingly stressed and competitive world. Whilst William J. Mitchell offers the education methodology developed for getting the best out of students at the Massachusetts Institute of Technology as a potential educational model for teaching and learning in general.